The Effect of Annona Muricata Leaves Towards Blood Levels of Cxcl9 and Lymphoblast (Study in Cerebral Malaria Phase of Swiss Mice) - Mohamed M.Y. Gadalla; Edi Dharmana; Kiss Jamiatun; Budi Laksono (Biosaintifika: Journal of Biology & Biology Education, 2015)
Cerebral malaria (CM) forms part of the spectrum of severe malaria, with a case fatality rate ranging from 15% in adults in southeast Asia to 8.5% in children in Africa. A.Muricata was used to cure Malaria in traditional medicine. The research will examine the effect of it in the chemokine (C-X-C motif) receptor 3 (CXCR3) binding chemokines, including chemokine (C-X-C motif) ligand 4 (CXCL4), CXCL9. The intervented mice group were infected then the it’s spleen were cultured , incubation 72 hours and then analyzed the result. The CXCL9 level of PbA-infected mice treated with A. muricata are lower than group of infected mice without treatment. Lymphoblast level of PbA-infected mice treated with A. Muricata are higher than group of infected mice without treatment. A. Muricata treatment cure in the CM in the mice and may be a potential treatment in human CM.Cerebral malaria (CM) adalah keadaan infeksi malaria yang berat dengan tingkat kefatalan dari 15% di Asia tenggara dan 8% di Afrika. A. Muricata secara tradisional dipakai mengobati CM. Riset ini meneliti pengaruh A. Muricata pada ikatan chemokine (C-X-C motif) reseptor 3 (CXCR3)termasuk chemokine (C-X-C motif) ligand 4 (CXCL4) dan CXCL9. Kelompok mice intervensi diinfeksi dan limfanya di culture dalam inkubator 72 jam untuk dianalisis. Kadar PbA CXCL9 pada mencit intervensi yang diberi A. Muricata lebih rendah dari pada kontrol. Kadar PbA limfoblast intervensi lebihtinggi dari pada kontrol. A. Muricata memperbaiki CM pada mencit dan berpotensi sebagai pengobat pada CM manusia.